The Effect of Different Litter Materials on Lactate Dehydrogenase (LDH) Content and Oxidative Metabolism in Broilers - Yildirim Koc, E (Journal of the Hellenic Veterinary Medical Society, 2024)
Footpad dermatitis and hock burn are dermatological problems with similar pathologies, also known as contact dermatitis. As a result, carcass quality and the rate of water and feed utilization due to lameness decreases. It was aimed to determine serum LDH level and oxidative metabolism change in footpad dermatitis and hock skin lesions that can occur in broilers due to different litter materials, and to seek serum LDH activity as a potential marker of footpad dermatitis in broilers, similarly to humans. The study was conducted in 3 climate chambers, one of which was conventional poultry litter (wood shavings), the other perforated plastic floor and the last was an addition of zeolite to wood shavings (6 kg/m2). The study followed a completely randomized design with three litter treatments replicated four times. A well ventilated house divided into 4 pans was used where each pan or a replicate contain 42 birds with a total of (n=168) birds (33 kg/m2). Regarding broiler feet health litter treatment had significant influence on footpad dermatitis while hock burns were not statistically different among litter treatments. Severe lesions on the footpad were most common in the zeolite group, while no severe lesions were observed in the plastic floor. Consistent with this result, the treatment of litter supplemented with zeolite significantly increased serum LDH level and footpad MDA activity. Interestingly, zeolite treatment also led to cause an increase in antioxidant enzymes (SOD, CAT, GSH) activities in footpads. Our current findings suggest that serum LDH level may be an indicator of the severity of footpad dermatitis. Higher oxygen free radical production, evidenced by increased MDA support to the oxidative stress in foot pad dermatitis. The increased activities of antioxidant enzymes may be a compensatory regulation in response to increased oxidative stress.